2021
DOI: 10.1021/acs.jpclett.1c01678
|View full text |Cite
|
Sign up to set email alerts
|

Universal Fluorination-Created Edge C–F Groups in Networks of Multidimensional Carbon Materials

Abstract: Fluorination can significantly change the physical and chemical properties of carbon materials (CMs). Common sense for the fluorination mechanism for CMs indicates that one basal-plane C−F group (CF group) can form as one fluorine atom bonded to one carbon atom along the out-of-plane carbon networks without creating edge C−F groups (including CF 2 and CF 3 groups) at vacancies in carbon networks. We report that fluorination can generally create edge C−F groups in multidimensional CMs such as graphite, graphene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 59 publications
0
7
0
Order By: Relevance
“…It is found that the spectrum at 280-296 eV exhibits two strong combined with two weak characteristic peaks. As to the two strong peaks, one peak at ∼285.8 eV is attributed to the C-CF bonds for carbons adjacent to CF bonds, and the other peak at ∼288.8 eV to the CF bonds for carbons to CF covalent bonds [3,10,[41][42][43]. As mentioned above, if fluorine clustering is present, the CF peak should be much stronger than C-CF peak.…”
Section: Structural Characterization and Analysismentioning
confidence: 90%
See 4 more Smart Citations
“…It is found that the spectrum at 280-296 eV exhibits two strong combined with two weak characteristic peaks. As to the two strong peaks, one peak at ∼285.8 eV is attributed to the C-CF bonds for carbons adjacent to CF bonds, and the other peak at ∼288.8 eV to the CF bonds for carbons to CF covalent bonds [3,10,[41][42][43]. As mentioned above, if fluorine clustering is present, the CF peak should be much stronger than C-CF peak.…”
Section: Structural Characterization and Analysismentioning
confidence: 90%
“…Reasonably, a fluorine cluster consists of two parts, the outermost fluorine shell and the inner fluorine core, as illustrated in figure 1(a). In the C 1s XPS spectrum of FG, the great difference in the binding energy of the sp 2 C-C peak, C-CF peak (for carbons adjacent to CF bonds), and CF peak (for CF covalent bonds) due to the strong binding energy shift relative to each other [3,10,[41][42][43], affords one to obtain the exact R [3,41]. In principle, the C-CF peak mainly results from the fluorinated carbons of the shell of the cluster, whilst, the CF peak mainly results from the fluorinated carbons of the core.…”
Section: Structural Characterization and Analysismentioning
confidence: 99%
See 3 more Smart Citations